AN OVERVIEW OF FISCAL CONSOLIDATION PROCESS IN THE EUROPEAN UNION - Bucur, Iulia Andreea; Muntean, Mircea (Studies and Scientific Researches. Economics Edition, 2014)
This paper aims to explore, based on theoretical and empirical research in the field and on data available on Eurostat and European Commission, in the context of financial significant imbalances and thus of the financial stress in the EU countries and especially in the Euro area, the main developments in the fiscal consolidation process given the fiscal effort of each country towards fiscal union. Since the financial crisis started in 2008, many EU Member States demonstrates an obvious macroeconomic imbalance which requires increased responsibility regarding fiscal developments. The impact of the crisis and the causes of sovereign debt high levels trends varied between EU countries as well as the budget deficit levels. Thus, the main priority for EU members must be the continuation of differentiated fiscal consolidation, given the specificities of each economy, favoring growth. The medium-term fiscal policy needs to focus on consolidating public finances along with restoring long-term sustainability.